Transcription of foreign personal names in the written works of learners of Latvian as a foreign language - Kļavinska, Antra (Journal of Education Culture and Society, 2021)
Aim. The aim of this study is to analyse how personal names are transcribed in the written works of Latvian as foreign language learners, as well as the most typical mistakes when transcribing personal names in other languages, the attitude of students towards the Latvianisation of their personal names, and the experience of Latvian language teachers in teaching the principles of transcribing personal names. Methods. The study uses the corpus analysis method, as well as a survey of students and survey of teachers who teach Latvian as a foreign language. The article includes error analysis of the personal name transcription established in the corpus and the analysis of the survey results. Results and conclusion. It was found out that students mostly know how to transcribe their names in Latvian; less frequently do they know how their surname should be transcribed. Their attitude towards Latvianisation of personal names is various: positive, negative or neutral. Latvian as a foreign language teachers emphasize the principle of transcription of foreign personal names and the need to provide its justification in the study process. It was concluded that further Latvian language acquisition process needs to be focused more on the problems with transcription of foreign personal names. Originality. This study highlights the aspect which is little researched in the applied linguistics – the issued linked to transcription of foreign personal names in the process of learning the Latvian language. The novelty is related to the use of a new resource (error-tagged learner corpus) data.